(untitled) (Journal of International Crisis and Risk Communication Research, 2022)
Combining the uses and gratifications theory (U&G) and the social-mediated crisis communication model (SMCC), this study examined why and how Chinese publics sought and shared information during a public health crisis in China—the Quanjian crisis. Through a survey of 309 Chinese adults, we found that Chinese publics sought and shared crisis information to gratify socializing, guidance, medium appeal, mood management, and habitual diversion gratifications. In addition, publics sought medium appeal gratification through information seeking and sought competence and reciprocity gratifications through information sharing. Moreover, the study examined the relationships between gratifications-sought and forms (i.e., traditional media, social media, offline word-of-mouth communication) and sources (i.e., government, news agency, health professionals, Quanjian company, other public members) of information that Chinese publics sought and shared during the Quanjian crisis.